Dose- and time-dependent renoprotection of Angelica sinensis in patients with chronic kidney disease: A longitudinal cohort study - Chen, Hsiao-Tien; Yu, Ben-Hui; Yeh, Ming-Hsien; Hung, Shih-Kai; Chen, Yi-Chun (Frontiers in Pharmacology, 2023)
Background: Based on their anti-oxidative and anti-fibrotic properties, Angelica sinensis (Oliv.) Diels roots [Apiaceae; Radix Angelicae sinensis] (Danggui [abbreviated as S in the context]), Astragalus membranaceus (Fisch.) Bunge [Fabaceae; Astragalus membranaceus] (Huangqi [A]), Rheum palmatum L. [Polygonaceae; Rheum palmatum] (Dahuang [R]), and Salvia miltiorrhiza Bunge [Lamiaceae; Salvia miltiorrhiza Bunge radix et rhizoma] (Danshen [D]) are potential renoprotective Chinese herbal medicines (CHMs). Renoprotection using ARD alone for the treatment of chronic kidney disease (CKD) has been documented in pre-clinical, clinical, and meta-analysis research; however, only pre-clinical data are available for the use of S alone. Moreover, with an increasing number of CKD patients taking prescribed CHMs, hyperkalemia risk remains unclear. Methods: This study retrospectively analyzed national health insurance claims data in 2001–2017. Propensity score matching was used to analyze renal and survival outcomes and the dose-response effects of S without ARD use in 18,348 new S users, 9,174 new ARD users, and 36,696 non-users. Cox proportional hazard regression was used to investigate adjusted hazard ratios (aHRs) for end-stage renal disease (ESRD) in the presence of competing mortality and death. The additive effect of the S herb in single form to compounds was also analyzed. Additionally, to analyze hyperkalemia risk, an exact match on each covariate was used to include 42,265 new CHM users and non-users, while Poisson regression was used to estimate adjusted incidence rate ratios (aIRRs) of hyperkalemia of prescribed CHMs. Results: S users and ARD users were associated with aHRs of 0.77 (95% confidence interval; 0.69–0.86) and 1.04 (0.91–1.19), respectively, for ESRD and 0.55 (0.53–0.57) and 0.71 (0.67–0.75), respectively, for death. The renal and survival benefits of S use were consistent in several sensitivity analyses. The dose- and time-dependent renoprotection and dose-dependent survival benefits were observed for S use. The top two additive renoprotective collocations of the S herb in compounds were Xue-Fu-Zhu-Yu-Tang and Shen-Tong-Zhu-Yu-Tang, followed by Shu-Jing-Huo-Xue-Tang and Shen-Tong-Zhu-Yu-Tang. Moreover, CHM users were associated with aIRRs of 0.34 (0.31–0.37) for hyperkalemia. Conclusion: This study suggests dose- and time-dependent renoprotection and dose-dependent survival benefits of the S herb in compounds and no increased hyperkalemia risk of the prescribed CHMs in CKD patients.